Instructors’ Perceptions of Intelligent Tutoring Systems and Their Implications for Studying Computer Programming in Omani Higher Education Institutions - Al-Shanfari, Lamiya; Abdullah, Shubair; Fstnassi, Tarek; Al-Kharusi, Sultan (International Journal of Membrane Science and Technology, 2023)
It is a serious problem that universities worldwide, especially in the middle east, have a high rate of failure in programming courses. To overcome this issue which could probably be due to students’ lack of engagement, motivation and problem-solving skills, the Intelligent Tutoring System (ITS) can be an effective tool for enhancing student learning. Despite its effectiveness, no prior research has been conducted on the impact of using ITS in higher education institutions in Oman. This study therefore investigates the perceptions of Omani University instructors to determine the levels of awareness, readiness and challenges among Omani higher institutions concerning their integration of ITS. Also, to investigate the reasons for the poor achievement of students in programming courses. We adopted two approaches in this study. First, quantitative research was conducted via a 5-point Likert scale questionnaire distributed to 59 programming instructors from different higher education institutions. Second, quantitative research was interviewing 10 instructors. Our questionnaire data reveal that most of the participants are aware of ITS’ effectiveness in the learning process. They believe that Oman’s higher education institutions are ready to adopt ITS if sufficient training and support is provided. Via text mining, our interview data illustrates the reasons behind poor performance in programming courses which includes English language barriers, deficient critical thinking, lack problem-solving skills and inadequate modes of teaching. This study clarifies the situation of higher educational institutions in term of their awareness, redness and the challenges that they may face in adopting ITS.